The use of inoculating modification to increase durability of cast stainless steel blanks to intergranular corrosion - E. N. Eremin; G. N. Minnekhanov; R. G. Minnekhanov (Омский научный вестник)
The problem of improving the quality of centrifugal pipes made of stainless steel is considered. It is proposed to tap ferro-titanium in a furnace under slag, after its deep deoxidation by REM-containing additive for receiving such pipes with high mechanical and service properties. Before tapping the melt from the furnace, the melt must be processed by nano-dispersed titanium carbonitride in the modifying briquette composition. Implementing the above conditions allows increasing the tensile strength of cast metal by 10–15 %, plasticity by 30–45 % with increasing resistance to intergranular corrosion (IGC) in the casting section.